ANALYSIS OF PORK SUPPLY CHAIN IN TRADITIONAL MARKET, ABIANSEMAL DISTRICT - S., Rahmat; Putri, B. R. T.; Sukanata, I W. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the supply chain channel for pork products in the traditional market of Abiansemal District, Badung Regency. The research method used is purposive sampling (deliberately). The sample of respondents in this study amounted to 40. Based on the pre-survey, the research location started from traditional markets so that there are several traditional markets in Abiansemal District including the following: Tegal Darmasaba Market, Sibang Gede Market, Mambal Market, Tenten Market, Blahkiuh Market. The method for taking samples is using snowball sampling technique. The data used are primary data and secondary data. The research was conducted from September to October 2021. The data analysis used in this study was descriptive analysis Food Supply Chain Network . The results of the analysis show that: (1) There are 3 flows in the pork supply chain in the traditional market of Abiansemal District, Badung Regency, namely financial (financial) flow, information flow, and material (product) flow. (2) There are several institutions involved in the pork supply chain at the research location, namely: breeders, pork collectors, slaughterers, meat traders, pork processed food stalls, final consumers. All members of the supply chain complement each other in the product movement process. Suggestion: It is hoped that the local government can help to stabilize pork prices. Meat traders should process meat into other processed products to increase added value and minimize losses if the meat is not sold out   Keywords : pork, traditional market, supply chain.